QUALITY ASSURANCE IN TECHNOLOGY MEDIATED DISTANCE EDUCATION - Omoniyi, Tayo (Sokoto Educational Review, 2020)
Distance education has been acknowledged as a viable strategy of reaching adult learner who has to contend with competing priorities of work, home and school. Indeed, it has been the major strategy of teacher education by the National Teachers Institute (NTI) Kaduna. The National Open University of Nigeria (NOUN) and many Universities in the country offer teacher education programmes via distance learning. Therefore, the thrust of this paper has been appraisal of the critical elements that constitute quality in distance education system such as staff competence and course Development, Delivery strategies, Assessment of learning/programmmes. Appropriate recommendations have been made, with the aim of establishing benchmark for assuring quality in the distance education system, and particularly because of its implication on the quality of teachers for the Nigerian School System. Practitioners and policy makers will find the article a useful guide in assuring quality delivery of distance education in Nigeria.